Glucagon-like peptide-1 receptor agonists inhibit the progression of malignant pleural effusion in obese mice by regulating the metabolism of pleural effusion - Ming-Ming Shao; Shu-Feng Dong; Qing-Yu Chen; Rui-Qi Wei; Feng-Shuang Yi (Journal of Translational Medicine)
Abstract Background Diabetes is a prevalent endocrine disease frequently linked to obesity and associated with an increased cancer risk and mortality. Malignant pleural effusion (MPE), a common metastatic manifestation of advanced cancer, poses significant challenges in clinical management. This study aimed to investigate the potential impact of glucagon-like peptide-1 receptor agonists (GLP-1RA), a novel type of therapeutic agents for diabetes, on the progression and metabolomic profile of MPE in an obese mouse model. Materials and methods A high-fat diet was used to induce obesity in mice, while normal diet-fed mice served as controls. Once obesity was established, a model of MPE was further established by intrapleural injection of mouse Lewis lung carcinoma cells. In a subsequent treatment experiment, the mice either received daily GLP-1RA injections at a dosage of 100 µg/kg or normal saline as a control treatment, from the establishment of the MPE model until the end of the experiment. Two weeks later, pleural liquid samples were collected and subsequently subjected to metabolomic profiling using liquid chromatography-tandem mass/mass spectrometry. Results Pleural liquid volume was significantly elevated in obese mice with MPE. GLP-1RA effectively reduced blood glucose levels, suppressed MPE progression, and extended survival time in these mice. Metabolomics analysis revealed that amino acid metabolism was suppressed in the MPE of obese mice, whereas GLP-1RA significantly enhanced nucleic acid metabolism, particularly purine metabolism, in the MPE of these mice. Notably, minimal influence on metabolic pathways within MPE was observed when treating normal-weight mice with GLP-1RA. Conclusions The findings offer a deeper understanding of the metabolic characteristics of MPE in obese mice and clarify the metabolic mechanism underlying the inhibitory effect of GLP-1RA on MPE progression in this population. These insights may provide theoretical support for designing innovative approaches in the treatment of cancer patients with obesity or diabetes.